(untitled) (Tanzania Medical Journal, 2022)
Background Although Tanzania has set a target of 90% Human Immunodeficiency Virus (HIV), retesting among pregnant women, the rate of re-uptake is still low despite the service being free of charge. This study determined HIV retesting among pregnant women with the gestational age of 36 weeks or higher attending the antenatal clinic at Temeke Regional Referral Hospital. Methods The cross-sectional study design was used. The data was collected from 12th October 2020 to 9th November 2020 in Temeke regional referral Hospital. Two hundred pregnant mothers attending the Reproductive and child health clinic (RCH) clinic who had a gestational age of 36 weeks or above and tested HIV negative from the first test were included. The demographic and obstetrics information were collected by using a structured questionnaire. The descriptive and factors analysis was done by using SPSS version 20. The Chi-square test determined the relationship between variables, and the P-value of less or equal to 0.05 was considered statistically significant. Results The percentage for re-uptake of second HIV test was 30% (60/200). Out of 60 who repeated the test, 6.7% (4/60) were HIV seroconverted. Factors associated with re-test were being married (p-value 0.05, X2=7.8), being self-employed (p-value is 0.00 , X2=18.838 ) ,four and above antenatal clinic visit (p-value is 0.003, X2=11.737 ) ,having knowledge of repeating (p-value is 0.00 ,X2=59.294) , multiparty ( p-value is 0.015 ,X2=8.334 ,positive perception during the first test (p-value is 0.044, X2= 4.039) ,maternal age of 25-29 years old (p-value is 0.053, X2= 10.901) ,and having access to radio and television (p-value is 0.04, X2= 6.442). Conclusion The proportion of HIV retesting was 30%, and factors associated with retesting were being married, being self-employed, more than four ANC visits, multiparity, having knowledge about retesting, and positive perception during the first test.